Participation of the C-Terminal Domain of RNA Polymerase II in Exon Definition during Pre-mRNA Splicing - Zeng, Changqing (American Society for Microbiology, 2000)
Interaction between transcription and pre-mRNA processing via binding of polymerase II (Pol II) to factors involved in capping, splicing, and polyadenylation has recently been demonstrated. The C-terminal domain (CTD), a highly phosphorylated repeat sequence of the largest subunit of Pol II, has been implicated in this interaction because deletion of this domain affects downstream RNA processing events and because it is the binding site for numerous processing factors. Here we show that recombinant CTD, free of other components of Pol II, activated in vitro splicing and assembly of the spliceosome in nuclear extracts if, and only if, the assayed precursor RNA was recognized via exon definition, i.e., if the substrates contained complete exons with both 3′ and 5′ splice sites. Furthermore, depletion of intact Pol II inactivated splicing of this set of precursor RNAs and addition of recombinant CTD restored activity. The added recombinant CTD was quickly hyper- and hypophosphorylated in extract, became associated with the precursor RNA, and stimulated the association of U1 snRNPs but not ASF/SF2 with substrate RNA. These observations suggest that the mode of interaction between the CTD and splicing factors is integrally tied to exon definition and the mechanism whereby distal exons can be recognized and brought into juxtaposition during assembly of the spliceosome.